2015
DOI: 10.1007/s00256-015-2204-7
|View full text |Cite
|
Sign up to set email alerts
|

First experience with single-source dual-energy computed tomography in six patients with acute arthralgia: a feasibility experiment using joint aspiration as a reference

Abstract: This initial experience suggests that S-DECT might be a valuable alternative to dual-source CT. Hence, more patients may benefit from its additional diagnostic abilities in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Recently, a raw-data-based monochromatic imaging technique was introduced on 320-row CT scanners (12). Previous studies reported that monochromatic high keV images are useful for metal artifact reduction (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a raw-data-based monochromatic imaging technique was introduced on 320-row CT scanners (12). Previous studies reported that monochromatic high keV images are useful for metal artifact reduction (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Dual-energy CT-based monochromatic imaging and a dedicated metal artifact reduction algorithm are the principal artifact reduction techniques (10,11). Recently, a raw-data-based monochromatic imaging technique was introduced on 320-row CT scanners (12). Previous studies reported that monochromatic high keV images are useful for metal artifact reduction (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The low-and high-energy data model tissue as a function of either two or three basis materials consisting of at least one low-atomic-number material and one highatomic-number material (eg, soft tissue and iodine). There are six commercially available DE CT acquisition schemes (2,7), including dual-source (8), rapid peak kilovoltage switching (9), dual-layered detector (10), split-filter (11), and sequential scanning (12) systems.…”
mentioning
confidence: 99%
“…Besides the study design, this false-positive result may be due to the quantity of the CPPD crystals that could be below the detection limit of DECT. A previous phantom study showed that single source DECT allowed reliable detection of CPPD crystals at concentrations of 6.25% or higher [ 17 ]. In the current study DECT detected CPPD crystals in a patient with severe osteoarthritis, although microscopic analysis did not found CPPD crystals in her joint fluid.…”
Section: Discussionmentioning
confidence: 99%
“…In general, x-rays having a different energy of the emitted photons are absorbed differently and therefore differ in attenuation in CT scans acquired with high or low tube voltage. Thus, a dual-energy gradient can be calculated, which characterizes this differing x-ray interaction and is relatively specific for a given material [ 14 17 ]. Recent studies reported that DECT was able to distinguish CPPD crystals from uric acid crystals and was useful to diagnose CPPD deposition disease, especially when crystal examination was not available or radiography was not easily interpretable [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%